Reunderstanding How to "Understand the Scripture" - Bridges, Matthew M. (Journal of theological interpretation, 2009)
When the disciples discover the empty tomb in John 20:9, the text offers a puzzling commentary on this discovery: "For they did not yet understand the scripture, that it was necessary that he rise from the dead." This commentary assumes a certain understanding of the OT yet does not point to a particular reference of the OT in the text of John, making this reference a difficult and confusing one. It is not, however, a sweeping transnarrative theme or an explicitly marked quotation of OT Scripture—none of the "marked" OT quotations concern the resurrection—that offers an answer to the puzzling comment. Rather, the solution comes out of the story of the raising of Lazarus. From this pericope (John 11:38–44), three proposals clarify the meaning of John 20:9. (1) In the Lazarus story, Jesus explicitly "prays" (John 11:41–42) a quotation of Ps 118:5, 21, 28. (2) The author further utilizes Ps 118 by drawing out the metaphor of the stone, a familiar Christological symbol, from the context of the quotation. (3) The stone, as a familiar but reconstituted symbol, literarily connects the Lazarus story with the resurrection story, and, by this connection, shows how the Gospel of John reads the resurrection from this one OT Scripture.